Writing on social networks: from permissiveness in cyberspace to the appropriation of written culture - Carvajal Barrios, Giovanna (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
The article presents the findings of a qualitative research that aims -among other objectives- to know what is the incidence of the degree of appropriation of the canon of writing in the way of writing of five young women, in three scenarios of cyberspace. A previous phase of the research is taken as a reference where it is tentatively stated that the way of writing in social networks is defined not only by media software and cyberspace, but also by the level of ascription to culture alphabetically written. The methodological tools correspond to the qualitative approach, although the particular analysis that the article deals with involves the analysis of numerical data. The text questions two affirmations of common sense: that non-canonical writing is a direct and inevitable consequence of the continuous use of social networks; and that technological endowment and digital literacy are sufficient to solve educational problems.